Perancangan Sistem Distribusi Data Antar Sistem Pada Sistem Informasi Sekolah Tinggi Teknik Cendekia (STTC) - Putera, Bintang Eka; Subali, Muhammad (Universitas Gunadarma, 2014)
The number of sub-systems which is part of System Information in Sekolah Tinggi Teknik Cendekia (SI-STTC) brings up a question of “how does the whole sub-system exchange information?”. Information exchange inter system needs a rule applying confidential aspects, data integrity and availability as system security standard. Based on the aspects, STTC designs a system named Intersystem Data Integrity System (SIDAS), a web service system designed by SOAP-XML architecture protocol. The system works on intermediate layer protocol so that it is considered to be used as inter sub-system data communication module. The design of SIDAS refers to the main aspect of computer security and business satisfaction aspect. The main aspect of computer security includes confidentiality, integrity, and availability aspect. Business satisfaction aspect refers to the criteria mentioned by COBIT as business need for information. The method used in the study includes two main parts namely business process analysis method and software development method. Business process analysis method includes analysis of business process rule and analysis of the STTC system user role, while software development analysis method use evolutionary development process model to adjust with the specification of development system done. The study produces a result of a system design which can be used as inter sub-system data integrator of System Information Sekolah Tinggi Teknik Cendekia (SI-STTC).Keywords: System Information, STTC, Web Service, Data Distribution, SOAP, XML